KEY ELEMENTS OF A SIMULATION MODEL OF HYDROLOGICAL FACTORSOF THE NORTHERN CASPIAN AS ENVIRONMENT HABITAT OF THE СTENOPHORA POPULATION MNEMIOPSIS LEIDY - A. M. Kamakin; C. V. Shipulin; D. N. Katunin (Юг России: экология, развитие, 2014)
Analysis of environmental situation in the Caspian and other basins (the Azov and Black Sea ones) showed that the development of an adequate simulation model of hydrological factors in the Northern Caspian as Mnemiopsis leidyi habitat was impossible without an up-to-date special data base. The main environmental factors that predetermine the annual invasion of the Northern Caspian byMnemiopsis leidyi subpopulation and its development are considered. At the present stage of monitoring investigations in the Caspian basin it is impossible to develop successful forecasts and a package of correct measures to reduce the negative impact of such an undesirable invader as Mnemiopsis leidyi on the Azov-Black Sea and Caspian basins without such a simulation model.